The Contribution of the Belarusian State University of Culture and Arts to the Development of Branding of the City of Minsk - Natalia V. Karchevskay; Aliaksandr A. Filipau (Управление культурой)
The article examines the potential contribution that the Belarusian State University of Culture and Arts can make to the branding of the city of Minsk. The article focuses on the fact that, despite a number of attempts, full-fledged branding of the Belarusian capital is still at the initial stage of its development; the existing potential of various city-forming institutions has not been fully used. In this context and subject to certain conditions, the Belarusian State University of Culture and Arts could play a significant role in the formation of the brand of the city of Minsk and its full promotion. The theoretical and partly empirical basis of the article was the existing comprehensive works on the issues of branding of places/cities, as well as individual examples of branding of Russian cities. In addition, the experience of past attempts to create a brand of the city of Minsk was carefully analyzed. To a large extent, the authors consider the branding of Minsk in the context of tourism development in the Republic of Belarus. Based on theoretical approaches to city branding, as well as a number of practical cases, the authors were able to analyze the potential of the Belarusian State University of Culture and Arts for the development of Minsk branding. The following were identified as elements of the university's potential contribution to this process: 1) Scientific support for the process of creating and popularizing the brand (due to the presence of highly qualified personnel); 2) The university as a center of attraction for creative youth from all over the country, a place for improving and realizing talents, a center for innovative and creative development; 3) Creation of a special space (on the territory of the university) as a concentration of the positive features of the city of Minsk; 4) Hospitality towards visitors; 5) Promoting a positive image of the country through a positive image of the city, and that, in turn, through a positive image of the university, using “soft power” mechanisms.